(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
Communication is an important 21st-century skill that learners need to learn in the classroom. Learning English as a second language is a must to become globally competent specifically in communicating with people. Using conventional teaching methods in this digital era may be insufficient to develop the learners’ potentials due to their natural exposure to advanced technologies. The use of gamification is an alternative strategy for 21st-century learners. This strategy helps learners not only in improving their performance but also their motivation. This study employed the quasi-experimental research design. The gamification strategy through the use of a mobile game in teaching ESL was tested among the 26 randomly paired students enrolled in Campus Journalism at Union Christian College. The respondents were divided into two groups: Group A as the experimental group and Group B as the control group. They were given a pre-test which became the basis of the researchers for coding a mobile game that was used for the gamification strategy. Afterward, gamification was implemented in the experimental group, while the conventional teaching strategy was implemented in the control group. A post-test was given after the implementation of the strategy. There was a significant improvement in the performance of the respondents in reading comprehension, grammar awareness, and vocabulary development after the gamification strategy implementation. The test scores of the experimental group in the three competencies ameliorated after the gamification strategy was implemented. Moreover, the difference between the test scores of the two groups of respondents is significant. Gamification used in three competencies namely Reading Comprehension, Grammar Awareness, and Vocabulary Development manifested positive outcomes. The results of the study show that the gamification strategy can help develop the ESL skills of the learners in the three areas: reading comprehension, grammar awareness, and vocabulary development. With this, gamification should be used as an alternative strategy in developing the ESL learning needs of students.